Devnagari Sign Language Recognition using Image Processing for Hearing Impaired Indian Students. (International Journal of Engineering and Computer Science, 2015)
Some people in society are hearing impaired due to which they can’t communicate with other people easily. Hand gesture is one of the most natural and expressive ways for the hearing impaired. Since people with hearing impairment or deaf people cannot talk like normal people so most of the time they have to depend on some sort of visual communication. Dumb people are usually deprived of normal communication with other people in the society. It has been observed that they find it really difficult at times to interact with normal people with their gestures, as only a very few of those are recognized by most people. Hand gesture is one of the most natural and expressive ways for the hearing impaired. Sign language is the primary means of communication in the deaf and dumb community. It also got grammar and vocabulary but uses visual modality for exchanging information. Normal people are usually unaware of sign language. E.g. American Sign Language (ASL) or Devnagari Sign Language. The gestures are of many types like hand gesture which include one hand, two hands and face gestures. Hand gestures can be classified in two categories: static and dynamic. A static gesture is a particular hand configuration and pose, represented by a single image. A dynamic gesture is a moving gesture, represented by a sequence of images. However, because of the complexity of dynamic gestures, most researches are focused either on static gestures, postures, or a small set of dynamic gestures.